Manajemen Pesantren sebagai Khazanah Tonggak Keberhasilan Pendidikan Islam - Ahmad Khori (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2017)
Management is one of the most important aspects in organizing an institution including educational institutions and especially Islamic education institutions and pesantren. Both institutions cannot be separated and are the benchmarks of Islamic education. History has proved that the embryo of formal education is the pesantren education which is started from family, mosques, and other public places. Since Islam grew rapidly, then education has been prioritized and even served as indoctrination. Pesantren, with its relentless inspiration, definite innovation, as well as bahtsul masa'il, mukhadloroh and sorogan as the characteristic of its teaching-learning and evaluation process is able to bear outstanding generation ready to solve contemporary problems Thus, the benefit of Islamic education can be taken the usefulness aspects of Islamic education outcomes can be grasped by the entire society. This is suggested by the works of the scholars/clerics (kyai) and students (santri) who continuously fortify themselves with virtuous deeds amidst the bustle of the current world